Pelaksanaan Program Desa Cerdas dalam Mendukung Pembangunan Digitalisasi di Nagari Bunga Pasang Salido Kabupaten Pesisir Selatan - Anita Zulman; Jumiati Jumiati (Policy, Law and Political Research Center, 2025)
This study aims to analyze the implementation of the smart village program in supporting digitalization development in Nagari Bunga Pasang Salido. This study uses a qualitative approach with descriptive methods, literature review, as well as interviews, observations, and documentation. The research findings show that the implementation of the smart village program is seen through 5 dimensions, including implementing all plans, policies that have been formulated and established, completing all the necessary needs and tools and who will implement the smart village program in the village. This program has been implemented in the form of accompanying activities in the program consisting of digital ambassadors, digital cadres, village officials, capacity building through various trainings. However, in its implementation it cannot be said to have achieved its full objectives and has not run optimally, this is seen in the lack of facilities and infrastructure to support community training activities, digitalization-based service governance and publication updates on the village website which are still minimal and the lack of networking or cooperation to support the sustainability of the program. Therefore, it is necessary for the optimal implementation of the program by encouraging technological progress in the village government sector, forming an adaptive, innovative, and participatory society in sustainable village development. Support from all parties, including local governments, non-governmental organizations, and the private sector, is essential to realizing smart villages.